A Polish Renaissance - Jacobson, Bernard (Phaidon Press, 1996)
Yet the four Poles whose story is told here - Andrzej Panufnik (1914-91), Witold Lutoslawski (1913-94), Krzystof Penderecki (b. 1933), and Henryk Gorecki (b. 1933) - are noted for their development of radically differing creative approaches, in spite of a common national background
Keywords: Panufnik, Andrzej -- 1914-1991; Górecki, Henryk Mikołaj -- 1933-2010; Penderecki, Krzysztof -- 1933-2020; Lutosławski, Witold -- 1913-1994; Geschichte 1900-2000; Geschichte 1900-; Componisten; Compositeurs - Pologne - Biographies; Musique - Pologne - 20e siècle - Histoire et critique; Muziekleven; Muziekwerken; Musik; Composers -- Poland -- Biography; Music -- Poland -- 20th century -- History and criticism; Polen; Biografie; Górecki, Henryk